FILSAFAT DAN ETIKA ADMINISTRASI DEMOKRASI DAN PERKEMBANGANNYA DENGAN TEKNOLOGI INFORMASI DAN KOMUNIKASI (TIK): WACANA DIGITALISASI DALAM PEMILIHAN UMUM DI INDONESIA TAHUN 2024 - Daniah Kholda; Putu Jodhita Putri (Kultura: Jurnal Ilmu Hukum, Sosial, dan Humaniora, 2023)
This essay seeks to examine digital democracy in the conduct of elections. Digital democracy aims to enhance political democracy and citizen participation in democratic processes. Digital democracy is an effort to implement democracy without spatial, temporal, and conditional constraints. The concept of digital democracy differs from traditional democracy, which is based on specific times, places, and conditions. The conduct of elections is one form of implementing democracy in a country, including Indonesia. The method used in composing an essay on the discourse of digitalization in the 2024 general elections employs a qualitative approach based on data and interview results published on social media. By emphasizing the perspective of participants, the research method used here differs from the rigid quantitative approach, positioning the researcher separately from the object under study. The research results indicate that, based on data from the Central Statistics Agency, individuals are considered part of Generation Z if they were born between 1997 and 2012. According to the population census, 27.94 percent of Indonesia's population is dominated by Generation Z, which actively operates social media. Data from the Central Statistics Agency is also supported by the Indonesian Internet Service Providers Association data in 2020, revealing that approximately 170 million Indonesians are actively using social media. This data also mentions that, on average, Indonesian society spends 3 hours and 14 minutes on social media. Therefore, the digitalization of elections can strengthen various aspects of democracy in Indonesia. With increased transparency and accountability through technology, the public can have greater trust in the integrity of the electoral process. Easier access to information can also enhance citizen participation in the democratic process, reinforcing the representative essence of elections. However, to uphold the essence of democracy, it is crucial to ensure that every step of digitalization adheres to principles of inclusivity and fairness, preventing the marginalization of any group. Data and technology security are also essential to thwart potential threats to the integrity of democratic processes. Thus, electoral digitalization in Indonesia can serve as an instrument that enriches and fortifies democracy while preserving the core values of participation and fairness.